"You Are Going to Die": Risky Truth-Telling in the Contemporary American Hospital - Rojo, Micah (Nursing philosophy, 2026)
This paper identifies two major challenges facing nurses as they work to care well for the dying. First, American medicine operates on the presupposition that life must be maintained and suffering reduced. Life-sustaining interventions aid in this endeavour by normalising and stabilising dying bodies. As a result, and to the detriment of the patient, death is obfuscated. Second, the nurse's attempt to tell the truth about a patient's dying is often disqualified by medical hierarchies that privilege physician's knowledge claims as more legitimate. These challenges are exemplified through a narrative account of my caring for Mr. J on the day of his death. Nursing's traditional response to the challenges of caring well for the dying, patient advocacy, aims for the nurse's protection and empowerment of the patient's freedom to choose, but fails to recognise the patient's freedom is formed and structured by a medical institution that serves to obfuscate death and maintain life. This paper proposes an alternative: the nurse parrhesiastes or courageous truth-teller. Living a life of truth and training for their own death, which invites their interlocutors to regard the parrhesiastes as possessing valuable knowledge, the parrhesiastes, with a duty and courage to tell the truth, expresses their life in plain words, critiquing medicine's obscuring of death and helping their patient prepare to die.